Green Production and Green Technological Innovation: A Theoretical Review - Üster, Zeynep (Zenodo, 2025)
Environmental threats such as global climate change, depletion of natural resources and environmental pollution have led businesses to develop sustainability-oriented strategies. In this context, green production, green technological innovation and green supply chain management (GSCM) concepts stand out as tools that play a critical role in ensuring environmental sustainability. The study addresses the effects of green production and innovation practices on the environmental, economic and competitive performances of enterprises and examines how these processes are integrated in the context of supply chain management. Based on a narrative literature review and conceptual synthesis, this study examines practices such as. sustainable production models, green product innovation, eco-design, green purchasing, reverse logistics and environmentally friendly supplier relationships. The findings show that green practices not only reduce environmental impact but also provide firms with significant contributions such as long-term competitive advantage, cost savings and brand reputation. In addition, it is understood that economic and organizational sustainability concerns are the determinants of firms' orientation towards green innovation rather than environmental motivations. In conclusion, green production, technological innovation and supply chain practices should be evaluated holistically to achieve sustainable development goals. To ensure this integrity, the study provides strategic recommendations for both businesses and policymakers and makes a theoretical contribution to the literature.

Küresel iklim değişikliği, doğal kaynakların tükenmesi ve çevre kirliliği gibi çevresel tehditler, işletmeleri sürdürülebilirlik odaklı stratejiler geliştirmeye yönlendirmiştir. Bu bağlamda yeşil üretim, yeşil teknolojik inovasyon ve yeşil tedarik zinciri yönetimi (GSCM) kavramları, çevresel sürdürülebilirliğin sağlanmasında kritik rol oynayan araçlar olarak öne çıkmaktadır. Çalışma, yeşil üretim ve inovasyon uygulamalarının işletmelerin çevresel, ekonomik ve rekabetçi performanslarına olan etkilerini ele almakta; bu süreçlerin, tedarik zinciri yönetimi bağlamında nasıl entegre edildiğini incelemektedir. Literatür taraması ve kavramsal senteze dayanan bu çalışma, sürdürülebilir üretim modelleri, yeşil ürün inovasyonu, eko-tasarım, yeşil satın alma, tersine lojistik ve çevre dostu tedarikçi ilişkileri gibi uygulamaları incelemektedir. Bulgular, yeşil uygulamaların sadece çevresel etkiyi azaltmakla kalmadığını, aynı zamanda firmalara uzun vadeli rekabet avantajı, maliyet tasarrufu ve marka itibarı gibi önemli katkılar sunduğunu göstermektedir. Ayrıca, firmaların yeşil inovasyona yönelmesinde çevresel motivasyonlardan çok, ekonomik ve kurumsal sürdürülebilirlik kaygılarının belirleyici olduğu anlaşılmaktadır. Sonuç olarak, sürdürülebilir kalkınma hedeflerine ulaşmada yeşil üretim, teknolojik inovasyon ve yeşil tedarik zinciri uygulamaları bütünsel bir yaklaşım içinde değerlendirilmelidir. Çalışma, bu bütünlüğü sağlamak adına hem işletmeler hem de politika yapıcılar için stratejik öneriler sunmakta ve literatüre teorik bir katkı sağlamaktadır.
Keywords: Finans; green production; Green Technological Innovation; Green Supply Chain; Yeşil Üretim; Yeşil Teknolojik Inovasyon; Yeşil Tedarik Zinciri; Green Production, Green Technological Innovation, Green Supply Chain; Finance